Mechanistic insights into regioselective polymerization of 1, 3‐Dienes catalyzed by a bipyridine‐ligated iron complex: A DFT study. Issue 17 (18th May 2016) - Luo, Lun; Kang, Xiaohui; Zhou, Guangli; Chen, Si; Luo, Gen; Qu, Jingping; Luo, Yi
Abstract : The regioselective polymerizations of isoprene and 3‐methyl‐pentadiene catalyzed by a cationic iron (II) complex bearing bipyridine ligand have been computationally studied. Having achieved an agreement between calculation and experiment, it is found that the open‐shell unpaired 3d‐electrons localize on Fe center rather than partially distribute on the redox‐active bipyridine ligand. The steric effect plays a more important role in controlling the regioselectivity in comparison with electronic factors. The deformation energy is mainly contributed by monomer and Fe‐alkyl moieties rather than the bipyridine ligands themselves, although noncyclopentadienyl ancillary ligands are often deformed in most insertion transition states for selective polymerization of olefin. © 2016 Wiley Periodicals, Inc. Abstract : DFT calculations indicate that steric effect plays an important role in the regioselectivity in the polymerizations of dienes catalyzed by a cationic bipyridine‐ligated iron(II) complex. The catalytically active species is found to be at the open‐shell quintuplet ground state with no spin distribution on the redox‐active bipyridiene ligand.